Education Systems Around the World - Porto, Gilson Jr (IntechOpen, 2020)
This book, "Education Systems Around the World", is a collection of reviewed and relevant research chapters that offer a comprehensive overview of recent developments in the field of social sciences and humanities. The book comprises single chapters authored by various researchers and edited by an expert active in the field of social studies and humanities. All chapters are unique but are united under a common research study topic. This publication aims to provide a thorough overview of the latest research efforts by international authors on social studies and humanities, and open new possible research paths for further novel developments.